The Information Ecosystem of Local Network Organizations – An Opportunity for the Development in the Region - Agnieszka BUDZIEWICZ-GUŹLECKA (Communications of International Proceedings, 2021)
As digital transformation of an organization steadily progresses, it is necessary to make everyone aware of the need to ensure an efficient flow of information in a network organization. The article attempts to define barriers for development of network organizations in the region. It defines such terms as a network, information ecosystem and network organizations supporting regional development. The following research methods were adopted during the research process: critical analysis of literature, heuristic method, selected quantitative methods, analysis of information ecosystem. The study points to basic barriers that prevent or hamper the development of network organizations, as seen from the point of view of experts and members of network organizations. The study also defines a model for the operation of network organizations in the information ecosystem.
Keywords: Information; Network Organizations; Information Ecosystem.